Farmer preferences of cattle breeds, their market values and prospects for improvement in West Africa: A summary review - Kamuanga, M.; Tano, K.; Pokou, K.; Jabbar, M.A.; D'Ieteren, G.D.M. (European Union, 2001)
The reviewed case studies were conducted between 1994 and 1997 by ILRI research teams in Burkina Faso, Cote d'Ivoire and Nigeria. The objectives were to evaluate farmers' preferences for cattle traits; to assess constraints and opportunities for in situ conservation of endangered cattle breeds, and to evaluate breed differences in cattle prices to ascertain the signals sent by livestock markets. Farmers' preferences for cattle traits were also examined from the perspectives of the type of production system or purpose for keeping cattle.